Optimasi Tata Letak Fasilitas Produksi Untuk Meningkatkan Produktivitas UMKM Kerupuk "Sayu Rasa" Menggunakan Metode Systematic Layout Planning - Arif Rahman; Deny Wibisono; Tulus Widjajanto (BULLET : Jurnal Multidisiplin Ilmu, 2025)
"Sayu Rasa" Crackers MSME faces productivity constraints due to suboptimal production facility layout, resulting in long material handling distances and inefficient production time. This study aims to optimize the production layout to minimize material handling distance and improve production process efficiency. The method used is Systematic Layout Planning (SLP) through stages of material flow analysis, from-to chart creation, activity relationship diagram design, layout alternative development, and evaluation using weighted factor analysis. Implementation results show a 39.1% reduction in material handling distance (from 128 meters to 78 meters per production cycle) and a 20% productivity increase (from 50 kg/day to 60 kg/day). Production time decreased by 15.5% from 420 minutes to 355 minutes for the same production capacity. The research conclusion proves that the application of industrial engineering principles through SLP method effectively improves MSME operational performance with minimal investment.